Impact of humidity, temperature and condensation on O2 and CO2 transmission rate of modified atmosphere packages - Z.A., Nur Hanani; Sonawane, A.D.; Mahajan, P.V. (Elsevier, 2023)
This study aimed to determine the effect of different conditions such as packaging materials, relative humidity, temperature and condensation on the transmission rate of gases inside the packages. Bioplastics Natureflex (N) film and petroleum-based material, polypropylene (PP) film were used to cover cylinders with different humidity conditions (0 , 50 , and 100 RH). Then, polypropylene was used to cover trays with modified gases and the effects of different packaging conditions on the transmission rate of polypropylene were determined using a modular sensor system. It was found that polypropylene had lower transmission rate values, albeit no significant difference. The relative humidity of the cylinders also gave no significant effect on the transmission rate values of bioplastics and polypropylene films. Nonetheless, the temperature of the storage contributed a significant (p < 0.05) impact towards transmission rate values of modified atmosphere packages, with lower temperature causing lower transmission rate values to both oxygen and carbon dioxide gases. Meanwhile, different packaging conditions with condensation and different humidity did not influence the transmission rate, as shown in the earlier findings. In conclusion, only certain factors affected the transmission rate of gases in the packages, however, the right variables and a proper storage for explicit foods are vital to ensure their safety and quality.